STRATEGI PENGEMBANGAN KERAMBA JARING APUNG BERKELANJUTAN DI WADUK PLTA KOTO PANJANG KAMPAR RIAU - Siagian, Madju (Jurnal Perikanan dan Kelautan, 2010)
A study on the strategy of the development of sustainable floating-net cagefisheries in the reservoir of Koto Panjang Hydro-electric Power Plant, Kampar, RiauProvince, was conducted on May-October 2009.. Based on its carrying capacity, thenumber of FNC units which can be exposed in the reservoir during the period of thestudy is 19,599 – 33,515. units. The existing utilization level for 900 KJA is actuallyabout 2.7-4.6 % of the capacity. This indicates that FNC is potential to be develoved.At the time of FNC research with operations in reservoirs are concentrated in theforbidden zone as compared with cultivation zone . The strategy of developmentfloating net cage in reservoir of Koto Panjang for the use of wastes, cultivationtechnology, and environmentally friendly quality feeding, so that the waste from FNCcan be reduced and the adversely impact can be minimized and the reservoir qualitycan be controlled up to floating net cage fisheries in the reservoir sustainable.